ANALISIS BENTUK DAN NILAI BUDAYA DALAM “SYAIR KESULTANAN SIAK” VERSI M. AMIROEDIN - Darusman A R (Madah: Jurnal Bahasa dan Sastra, 2014)
In the background of Malay community, poem is not the only entertaiment media but it is also an effort of contiuning regional culture to grasp moral-historical messages implied in the form and cultural values of the text of the poem.This research is an analyses  of structural  work of traditional Malay poem toward the use of line pattern and cultural values of text of Kesultanan Siak poem. This is a descriptive research with a content analyses  approach wich is analyszed in the point of view of form related to the use of the number of word order and syllables in the line pattern of the poem text while the cultural values related to the culture of Riau. Regional Malay implies religiosity customary values and the values of  tradition. Dalam latar belakang masyarakat Melayu, puisi bukan satu-satunya media hiburan tetapi juga merupakan salah satu upaya dalam mengembangkan kebudayaan daerah untuk mengambil pesan-pesan moral-sejarah yang tersirat dalam bentuk dan nilai budaya teks puisi. Penelitian ini adalah analisis struktur karya sastra dari puisi tradisional Melayu terhadap penggunaan pola baris dan nilai-nilai budaya teks puisi Kesultanan Siak. Penelitian ini merupakan penelitian deskriptif dengan pendekatan analisis konten  dalam sudut pandang bentuk yang berkaitan dengan penggunaan jumlah urutan kata dan suku kata dalam pola baris teks puisi sementara nilai-nilai budaya adalah yang terkait dengan budaya Riau. Daerah Melayu menyiratkan religiositas nilai-nilai adat, keagamaan, dan tradisi.